Knowledge, awareness, practices and adherence to treatment of patients with primary hypothyroidism in Delhi - Pradeep Kumar; Deepak Khandelwal; Suresh Mittal; Deep Dutta; Sanjay Kalra; Pratima Katiyar; Vivek Aggarwal (Indian Journal of Endocrinology and Metabolism, 2017)
Background: There is a paucity of data on knowledge, awareness, and practices (KAP) of patients with hypothyroidism in India. Aims and Objectives: To study the KAP and adherence to treatment of participants with primary hypothyroidism. Materials and Methods: An observational cross-sectional study was conducted in Endocrinology Outpatient Department of Maharaja Agrasen Hospital, Punjabi Bagh, New Delhi. Two-fifty consecutive primary hypothyroidism participants, aged ≥18 years, who were on treatment for at least 3 months responded to a structured questionnaire, to assess their KAP about the disease and adherence to treatment. Results: A total of 250 patients completed the questionnaire. The mean age of the participants was 43.24 ± 10.80 years; with majority being females (85.6%). The median duration of hypothyroidism was 8 years (range: 3–10). Most were well educated, with 53.6% being graduates/postgraduates. Knowledge and awareness related to hypothyroidism was poor in majority of participants. Only 35.2% and 51.2% knew correct meaning of the terms “thyroid” and “hypothyroidism” respectively. Only 25.6% participants knew correctly that thyroxine (T4) is used to replace and normalize blood levels of thyroid hormone. Forty percent had false dietary beliefs in the context of hypothyroidism. Ten percent participants felt T4 can be stopped once laboratory reports return to normal. Only 36.4% participants knew correctly that T4 need to be continued during pregnancy. Many participants (30.4%) believed hypothyroidism can lead to weight gain in excess of 10 kg. Regarding adherence, 90.4% participants were adherent to T4, 2.4% were moderately adherent, and remaining 7.2% participants were nonadherent to T4. Conclusion: A large number of patients with primary hypothyroidism lack basic knowledge about disease and have dietary and treatment-related prejudices and poor treatment adherence. Public health measures are required to improve KAP in patients with primary hypothyroidism.